A Translation into English of AL-FUZAI’s1 “Breakdown Time”2 - Dohal, Gassim H. (Advances in Social Sciences Research Journal, 2021)
Khalil I. Al-Fuzai (1940- ) is a Saudi writer who published few collections of stories. In these stories he manages to introduce his Arabian society in a simple, frank way (see Dohal 2013). One of these stories is “Breakdown Time.” I chose to translate this story for it is a good representation of what Al-Fuzai has written (Dohal, 2018 & 2019). In addition, it is about the Arabian culture; it tells how a man can propose for a woman’s hand.